The "Belt and Road Initiative": impacts on TEN-T and on the European transport system - Dick Dunmore; Alberto Preti; Clémence Routaboul (Journal of Shipping and Trade (JST), 2019)
China's Belt and Road Initiative, announced in late 2013, includes the construction of land-based transport connections between Asia and Europe, the creation of an economic belt for Eurasian cooperation, and maritime routes between China and all continents with which it may trade. Within the European Union, it will interact with infrastructure and services provided in the private sector, by the Member States, and by the European Union including through the Trans-European Transport Network programme. This paper focuses on the scope for rail services between China and Europe to attract freight currently travelling by sea and air, and the resulting changes in relative accessibility and competitive attractiveness of different maritime and landlocked regions of Europe. It estimates that, by 2040, 3 million TEU of freight between the Far East and Europe might travel by rail, comprising 2.5 million TEU from sea and 0.5 million TEU from air. While it concludes that it is not possible to predict whether and where these transfers will require changes to the Trans-European Transport Network programme, it describes recommendations on how the programme should take the Belt and Road Initiative into account.
Keywords: 650; Belt and road initiative; BRI; Trans-European transport network; TEN-T; Rail freight; Capacity constraints; Maritime freight